Therapeutic Targeting of Th17/Tc17 Cells Leads to Clinical Improvement of Lichen Planus - Solimani, Farzan; Pollmann, Robert; Schmidt, Thomas; Schmidt, Ansgar; Zheng, Xiang; Savai, Rajkumar; Mühlenbein, Stefan; Pickert, Julia; Eubel, Verena; Möbs, Christian; Eming, Rüdiger; Hertl, Michael (Frontiers in Immunology, 2019)
Lichen planus (LP) is a common, chronic relapsing inflammatory disorder of the skin and mucous membranes which often poses a major therapeutic challenge due to its refractory course. Novel pathogenesis-based therapies are urgently needed. As several studies have shown that IL-17 may contribute to LP pathogenesis, we investigated whether therapeutic targeting of IL-17+ T cells leads to clinical improvement of mucosal and cutaneous LP lesions. A total of 5 patients with lichen planus were treated in a compassionate use trial with either secukinumab (anti-IL-17; 3 patients with acute and chronic recalcitrant muco-cutaneous LP), ustekinumab (anti-IL-12/IL-23; 1 patient with recalcitrant oral LP) or guselkumab (anti-IL-23; 1 patient with recalcitrant oral LP). The clinical course of the patients was assessed by the Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) reflecting both extent and severity of disease and functional sequelae of oral involvement for at least 12 weeks. The inflammatory infiltrate in lesional and post-lesional skin was analyzed by immunohistochemistry before and after treatment. Furthermore, the cytokine profile of peripheral blood T cells from the treated patients was assessed by flow cytometry and/or ELISpot assay. Treatment with secukinumab induced rapid and prolonged clinical amelioration of muco-cutaneous LP. Clinical improvement was accompanied by a strong reduction of the Th1 and Th17/Tc17 cellular mucosal and cutaneous infiltrate. Moreover, long-term treatment of one patient with recalcitrant oral LP with ustekinumab led to healing of the ulcerative oral lesions and a reduction of peripheral blood and lesional IL-17+ T cells. Finally, treatment with guselkumab led to a marked clinical improvement in a patient with recalcitrant erosive oral LP. These findings show for the first time that therapeutic targeting of Th17/Tc17 cells leads to a pronounced clinical amelioration of mucosal and cutaneous LP and strongly suggests that IL-17-producing T cells are central to disease pathogenesis. Thus, therapeutic targeting of Th17/Tc17 cells opens new therapeutic avenues in the treatment of recalcitrant LP.